2017
DOI: 10.1111/coep.12266
|View full text |Cite
|
Sign up to set email alerts
|

Will German Banks Earn Their Cost of Capital?

Abstract: Research QuestionThis paper analyses the effect of a sustained period of low interest rates on the outlook for the German banking sector. Low interest rates provide a particular challenge for German banks, which are highly dependent on interest income and exhibit relatively high cost-income ratios.It is thus an open question whether German banks will manage to earn their cost of capital in this environment. ContributionWe analyse the interest earnings from loans and the interest expenses for deposits, i.e. the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…Falling bank profits, which are under pressure in the ultra-low interest rate world, are a third mechanism (Dombret et al 2017). In this environment, banks' profit margins from lending long (to loan customers) and borrowing short (on financial markets) are being squeezed by a flattening yield curve (Deutsche Bundesbank 2016c, pp.…”
Section: Ultra-low Interest Rates and Why We Should Be Thinking Aheadmentioning
confidence: 82%
See 2 more Smart Citations
“…Falling bank profits, which are under pressure in the ultra-low interest rate world, are a third mechanism (Dombret et al 2017). In this environment, banks' profit margins from lending long (to loan customers) and borrowing short (on financial markets) are being squeezed by a flattening yield curve (Deutsche Bundesbank 2016c, pp.…”
Section: Ultra-low Interest Rates and Why We Should Be Thinking Aheadmentioning
confidence: 82%
“…In light of lowered returns in the face of ultra-low interest rates, banks need to recoup the forgone income (Dombret et al 2017). There is evidence of German banks taking on riskier loans to boost their profits (Deutsche Bundesbank 2015), which may very well represent a trend towards increased search for yield among German banks.…”
Section: Risks Of a Housing Bubble Have Increasedmentioning
confidence: 99%
See 1 more Smart Citation
“…Bendavid, Herer and Yücesan (2017) observed that firms might have a specific ration of short-term liabilities if its financing structure they feel is optimum in enhancing performance and profitability. Dombret, Gündüz and Rocholl (2019) observed that firms which had high short term debt levels when compared to their long term debt performed better than their competitors Kumar and Kaushal (2017) established that the use of short-term liabilities such as trade payables and accruals could have a positive effect to the productivity of the organizations since such sources of financing may be less costly to the business than the longer-term sources of funds. Further, short term sources of funds may have a positive influence on profitability due to the reduced contractual engagements that are involved.…”
Section: Short Term Debtmentioning
confidence: 99%
“…Liquidity risks stemming from financial markets have recently gained in importance, as concerns about possible effects on the international corporate bond market are feared (IMF (2015)). Among many other consequences, a dry-up of liquidity could affect the profitability of banks through higher funding costs and make it even more difficult to earn their cost of capital (see Dombret, Gündüz, and Rocholl (2017) and Dombret (2017b)). Furthermore, a liquidity shock could affect bank lending and materialize in either a reduction in loan volumes or higher credit spreads -both of which can have a severe negative impact on the real economy.…”
Section: Introductionmentioning
confidence: 99%